Colour-centred Release Hallucinations in a Patient with Early Parkinson's Disease and Unrecognised Autosomal Dominant Optic Atrophy. (4th July 2021) - Hardwick, Marc; Heath, Dominic; Saha, Romi; Cooper, Sarah
ABSTRACT: Visual hallucinations in Parkinson's disease (PD) are usually attributed to medications and dysfunction in higher order sensory processing as the disease progresses. However deficits in visual processing, including colour discrimination, have been reported in early, untreated PD and it is unclear how these, along with co-morbid conditions affecting vision, could contribute to hallucinations. This case describes a 66-year-old otherwise fully independent woman with early, mild PD who presented with discrete episodes of unusual vivid hallucinations centred on colour. She was later found to have a subclinical colour deficiency in excess of her PD and, after reporting a lifelong history of poor vision in her father, tested positive for autosomal dominant optic atrophy. This case illustrates how a lifelong extrinsic deficiency in colour vision can interact with the effects of visual changes in early stage PD and medication to provoke colour hallucinations. It therefore emphasises the importance of full ophthalmological work up in similar cases where hallucinations are atypical and unexpected for the severity and stage of PD.